The Correlation of Nurse's Work Environment with Missed Nursing Care in Hospital - Putri, Dinda Amalia Okvie; Rusca Putra, Kuswantoro; Lukitasari, Mifetika (Fundamental and Management Nursing Journal, 2022)
Introduction: Missed nursing care is caring aspect needed for patients who have intentionally or not been eliminated or significantly postponed. One of the factors that can affect missed nursing care is the work environment of the nurse. This study aims to examine the correlation of nurse's work environment with missed nursing care in a regional general hospital in Indonesia. Method: This research study is used correlational analysis and a cross sectional design approach which was carried out on 56 nurses as respondents using two instruments: Misscare survey and Practice environment scale- nursing work index (PES-NWI) questionnaire. Descriptive and inferential statistics tests were applied. The level of significancy was set at p value = <0.05. Results: Nurse work environment data including staffing and resources; quality of basic nursing care; nurse-doctor relationship; nurse participation in hospital affairs; nurse manager abilities, leadership, and nurse support. The statistical test showed study using Spearman Rank test showed that there was a significant relationship between the work environment of nurses and missed nursing care (Ï <0.05). Conclusions: Professional nursing environments determine the quality of care and patient outcomes. Assessing the quality of environments is essential to improve and obtain better health outcomes. Simplifying and shortening the way to evaluate environments reliably is also essential to help nurses better understand the strengths and weaknesses of their work. Identifying elements of nursing environments would allow the construction of better health services as a whole.